Mecanismo de transmissão da política monetária : uma análise do canal de crédito para a economia brasileira pós real - Silva, Tatiele Lacerda da (2012)
The present study aimed to examine the existence and relevance of the credit channel, the channel being divided between bank lending and balance sheet channel, the transmission of monetary policy in Brazil from January 2001 to July 2011, for this was used IPCA and IGP-DI. The methodology analyzes the Vector Auto-Regressive (VAR), as Granger causality tests, impulse function and response, variance decomposition analysis and speeds, and this, coming from the test Vector Error Correction (VECM .) The results show the credit channel, bank loans in the segment, important and relevant to raise economic growth, but with greater significance using the IGP-DI, and sustainable over time and an auxiliary channel to channel the money. Since the channel of the balance sheet, despite showing that increases the production of the economy, a channel is negligible, but significant, even if a channel has little development, and most influential currency, securities and exchange. Can not correspond to say that an auxiliary channel of the coin. And that use of the IPCA collaborates with the results of the IGP-DI increasing the production of the Brazilian economy to its potential level. The research concludes that there is in the Brazilian economy during this period, the four transmission channels of monetary policy.